HAK KREDITOR DENGAN TAGIHAN PIUTANG TERTOLAK DALAM PROSES PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - Sihabudin Sihabudin; Edo Adhitama (Arena Hukum, 2023)
One of the stages in delaying payment of receivables obligations (PKPU) is the verification of receivables. There may be a possibility that the claim for receivables being rejected at the verification stage may occur, but there is no legal remedy that can be taken by the creditor, either ordinary or extraordinary legal remedies. This article aims to analyze the legal protection of creditors' receivables which are rejected at the receivables verification stage by administrators in the PKPU process and the authority of the supervisory judge in terms of the creditor's bill being rejected at the receivables verification stage. This normative research uses a statutory approach. The results show that Law Number 37 of 2004 does not regulate legal remedies if receivables are rejected in the accounts receivable verification. Efforts are made when this happens, the supervisory judge has the authority to reconcile creditors and debtors in determining. Thus, the debtor does not need to wait for the emergence of a settlement homologation if the bill is rejected in the verification of receivables to submit an appeal to the Supreme Court.